2022
DOI: 10.5194/egusphere-egu22-1994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamical dependencies at monthly and interannual time scales in the Climate system: Study of the North Pacific and Atlantic regions

Abstract: <p>The directional dependencies of different climate indices are explored using the Liang-Kleeman information flow in order to disentangle the influence of certain regions over the globe on the development of low-frequency variability of others. Seven key indices (the sea-surface temperature in El-Niño 3.4 region, the Atlantic Multidecadal Oscillation, the North Atlantic Oscillation, the North Pacific America pattern, the Arctic Oscillation, the Pacifid Decadal Oscillation, the Tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…As mentioned above the NTA index uses SST anomalies that have been smoothed thus filtering out the response to NAO. An influence of NAO on AMO and NTA was found in Vannitsem and Liang (2022), and a possible reason for the difference with our results is that the NTA index used in Vannitsem and Liang (2022) is different from the one we use here, as our index is smoothed by a 3-month window.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…As mentioned above the NTA index uses SST anomalies that have been smoothed thus filtering out the response to NAO. An influence of NAO on AMO and NTA was found in Vannitsem and Liang (2022), and a possible reason for the difference with our results is that the NTA index used in Vannitsem and Liang (2022) is different from the one we use here, as our index is smoothed by a 3-month window.…”
Section: Discussioncontrasting
confidence: 96%
“…It was found that changes in Arctic sea ice are mainly driven by air and sea-surface temperatures and ocean heat transport. The rate of information flow was also used in Vannitsem and Liang (2022) to assess directional dependencies of seven climate indices and three local Belgium time series, on time scales from a month to five years. Among other results, the authors found that the Arctic Oscillation plays a key role on the dynamics of the North Pacific (NP) and North Atlantic (NA) on short (monthly) time scale, while NAO plays a role on long time scales (several years).…”
Section: Introductionmentioning
confidence: 99%